2019
DOI: 10.3389/fpsyg.2019.01910
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effect of Music Training on the Enhancement of Executive Function in Preschool Children

Abstract: Musical training is an enrichment activity involving multiple senses, including auditory, visual, somatosensorial, attention, memory, and executive function (EF), all of which are related to cognition. This study examined whether musical training enhances EF in preschool children who had not undergone previous systematic music learning. This study also explored the after-effects 12 weeks after cessation of musical training. Participants were 61 preschool children from a university-affiliated kindergarten in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 87 publications
6
32
0
2
Order By: Relevance
“…Our results show that music training may be more beneficial for attention and executive memory processes, which is indicated by enhanced DS backward scores. This supports previous findings of positive associations of music expertise with the DS backward task ( Guo et al, 2018 ) and higher cognitive functions, such as WM ( Roden et al, 2014 ; D’Souza et al, 2018 ) and other executive functions ( Degé et al, 2011 ; Saarikivi et al, 2016 ; Jaschke et al, 2018 ; Shen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show that music training may be more beneficial for attention and executive memory processes, which is indicated by enhanced DS backward scores. This supports previous findings of positive associations of music expertise with the DS backward task ( Guo et al, 2018 ) and higher cognitive functions, such as WM ( Roden et al, 2014 ; D’Souza et al, 2018 ) and other executive functions ( Degé et al, 2011 ; Saarikivi et al, 2016 ; Jaschke et al, 2018 ; Shen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies implemented interventions that may have been too short and, therefore, unable to observe the enhancement. For example, in Guo et al’s (2018) study, the training sessions lasted for only 6 weeks; in Shen et al’s (2019) study, the training program duration was 12 weeks. Some studies ( Lee et al, 2007 ; Schellenberg, 2011 ; Suárez et al, 2016 ) were cross-sectional and directly compared musically trained and untrained children or adults, which may make it difficult to draw conclusions regarding causation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, some researchers believe that the components of EF are independent of each other, including two-factor models (Monette et al, 2015) and three-factor model (Espy et al, 2004;Miller and Best, 2010;Hughes, 2011;Skogan et al, 2015). According to previous researchs on the EF training of preschool children (e.g., Lakes and Hoyt, 2004;Schonert-Reichl et al, 2015;Rosas et al, 2019;Shen et al, 2019), researchers mainly focus on three basic components.…”
Section: Executive Functionmentioning
confidence: 99%
“…Some studies have shown that music training can stimulate the activity of the cerebral cortex, and short-term training for 6 months can significantly improve behavior and change the growth of synapses, showing that music training can change the plasticity of the brain (Sylvain et al, 2009). Shen et al (2019) conducted 12 weeks of integrated music training for young children who had not previously received any music learning, the control group did not train. After the training, children in the music training group and children in the control group were tracked and tested.…”
Section: Music Trainingmentioning
confidence: 99%
“…Because these studies showed within-nonmusicians differences in levels of load of executive function for different complexity of tapping, the relationship between the previous findings and our between-groups difference cannot be clearly interpreted. Since musical performance requires motor planning and monitoring of finger movement (Palmer and Drake, 1997;Moreno et al, 2011;Shen et al, 2019;Colombo et al, 2020;Guo et al, 2021), we suggest that musicians perform finger taps with higher executive involvement compared to non-musicians even when they are simple ones. The higher levels of executive function in musicians can be maintained by the same processes to enable masterful temporal and ordinal precision of finger movements, together with fine-grained finger force control.…”
Section: The Effect Of Lifelong Musical Training: From Skillful Tapping To Cognitionmentioning
confidence: 94%